Formal Semantics of an Entity-Relationship Query Language - Hohenstein, Uwe; Engels, Gregor (Proceedings of the 9th International Conference on Entity-Relationship Approach (ER 90), Lausanne, Switzerland)

Elementary Actions on an Extended Entity-Relationship Database - Engels, Gregor (Proceedings of the workshop on Graph Grammars and Their Application to Computer Science (1990), Bremen (Germany))
Semantic data models have been widely studied for the conceptual specification of databases. However, most of these data models are restricted to the description of the static structure of a database. They do not provide means to specify the dynamic behaviour of a database. This paper sketches a language for the specification of actions on databases which have been specified by an Extended Entity-Relationship (EER) schema. These actions are based on so-called elementary actions, which are automatically be derived from the EER schema. So, it can always be guaranteed that these schema dependent elementary actions preserve all inherent integrity constraints. The semantics of the elementary actions is given in two steps: First, it is shown how the semantics of a database schema, i.e., a current database state, can be represented by an attributed graph. Then, the semantics of elementary actions is given by programmed graph replacements.

Konzepte einer Software-Architektur-Beschreibungssprache - Ebert, Jürgen; Engels, Gregor (Software-Entwicklung: Konzepte, Erfahrungen, Perspektiven, Fachtagung, 1989, Marburg (Germany))

CADDY-O: Syntaxgestütztes, graphisches Entwerfen konzeptioneller Datenbankschemata - Engels, Gregor (Tagungsband GI-Fachtagung "Interaktive Schnittstellen für Informationssysteme", TU Clausthal, Notizen zu Interaktive Systeme)

CADDY: Computer-Aided Design of Non-Standard Databases - Engels, Gregor; Hohenstein, Uwe; Hülsmann, Klaus; Löhr-Richter, Perdita; Ehrich, Hans-Dietrich (Proceedings of the International Conference on System Development Environments & Factories, Berlin, Germany)

Benutzerschnittstelle und Architektur der integrierten Datenbankentwurfsumgebung CADDY (Kurzfassung) - Engels, Gregor

Programmentwicklungsumgebungen: Konzepte und Realisierung - Engels, Gregor; Schäfer, Wilhelm

A Highly Integrated Tool Set for Program Development Support - Engels, Gregor; Janning, Thorsten; Schäfer, Wilhelm (Proceedings of the conference on ACM SIGSMALL/PC symposium on ACTES (SIGSMALL 1988), Cannes (France))
This paper describes the design of the integrated user interface of the software development environment IPSEN (Integrated Programming Support Environment). We explain the characteristic features of the IPSEN user interface, namely the structured layout of the screen, the command-driven tool activation, and especially the highly integrated use of the IPSEN tool set. We demonstrate those features by taking a sample set of tools of the IPSEN environment. That tool set supports all the programming-in-the-small activities within IPSEN. Finally, we sketch the realization of two prototypes running on an IBM-AT and a net of SUN workstations.

Konzeption einer integrierten Datenbank-Entwurfsumgebung - Engels, Gregor; Hohenstein, Uwe; Neugebauer, Leonore; Saake, Gunter; Ehrich, Hans-Dietrich (Proceedings of DBTA/SI Data Dictionaries und Entwicklungswerkzeuge für Datenbank-Anwendungen, Zürich, Switzerland)

Auf dem Weg zu einer integrierten Datenbank-Entwurfsumgebung - Engels, Gregor; Hohenstein, Uwe; Saake, Gunter; Ehrich, Hans-Dietrich (Proceedings of the GI-Workshop on "Sprachspezifische Programmierumgebungen")